If a cosecΦ=b and a cotΦ=c,prove that a²+c²=b²
Answers
Answered by
3
Step-by-step explanation:
a cosecΦ= b, a cosecΦ=b/a
a cotΦ= c, cotΦ= c/a
Using,
cosec²Φ - cot²Φ= 1
=>b²/a² - c²/a² = 1
=> (b²-c²)/a² = 1
=> b² - c² = a²
=> b² = a² + c² (Hence proved)
Answered by
2
The answer is attached.
It has used the identity cosec theta = cot theta + 1
Attachments:
![](https://hi-static.z-dn.net/files/dc1/d86c3df4ed0b716c3103238e8293d311.jpg)
Similar questions
Accountancy,
2 months ago
Math,
2 months ago
Biology,
2 months ago
World Languages,
1 year ago
Science,
1 year ago